Economic impacts of repowering wind turbines: a comparative analysis of advanced wind turbine technologies - Dorcas Mikindani; Peter Deeney; Niall P. Dunphy (Sustainable Energy Research)
Abstract Many of Europe’s wind farms are nearing the end of their operational lives, threatening overall wind energy capacity. This study examines wind turbine repowering as a solution, particularly through the deployment of advanced turbine technologies. It compares the novel X-ROTOR turbine with traditional horizontal axis wind turbines (HAWT) using the International Jobs and Economic Development Impact (I-JEDI) model to assess regional impacts of deploying 5GW capacity. Results suggest that X-ROTOR offers notable cost advantages, which can improve the economic viability of wind farms particularly under manufacturing localization scenarios. Sensitivity analyses confirm that these outcomes are consistent across a range of manufacturing input assumptions, supporting the robustness of the findings. This research highlights the potential of innovative turbine technologies to boost energy efficiency, reduce costs, and support the EU's decarbonisation goals.